2013
DOI: 10.1128/aem.02883-12
|View full text |Cite
|
Sign up to set email alerts
|

Systems Engineering of Tyrosine 195, Tyrosine 260, and Glutamine 265 in Cyclodextrin Glycosyltransferase from Paenibacillus macerans To Enhance Maltodextrin Specificity for 2- O - d -Glucopyranosyl- l -Ascorbic Acid Synthesis

Abstract: In this work, the site saturation mutagenesis of tyrosine 195, tyrosine 260 and glutamine 265 in the cyclodextrin glycosyltransferase (CGTase) from Paenibacillus macerans was conducted to improve the specificity of CGTase for maltodextrin, which can be used as a cheap and easily soluble glycosyl donor for the synthesis of 2-O-D-glucopyranosyl-L-ascorbic acid (AA-2G). Specifically, the site-saturation mutagenesis of three sites-tyrosine 195, tyrosine 260, and glutamine 265-was performed, and it was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…As shown in Fig. 2A, the optimal temperature for AA-2G production with the wild-type CGTase was 36°C, which was also reported in our previous studies (8)(9)(10) and is similar to the optimal temperature for ␣-CGTase-catalyzed AA-2G synthesis with ␤-cyclodextrin as the glycosyl donor (6). However, SAP5-CGTase and SAP6-CGTase produced the highest AA-2G titer at 28°C, and this optimal temperature is the same as that of production with the chimeric enzymes CGT-CBM Amy and CGT⌬E-CBM Amy (11).…”
Section: Methodssupporting
confidence: 51%
See 1 more Smart Citation
“…As shown in Fig. 2A, the optimal temperature for AA-2G production with the wild-type CGTase was 36°C, which was also reported in our previous studies (8)(9)(10) and is similar to the optimal temperature for ␣-CGTase-catalyzed AA-2G synthesis with ␤-cyclodextrin as the glycosyl donor (6). However, SAP5-CGTase and SAP6-CGTase produced the highest AA-2G titer at 28°C, and this optimal temperature is the same as that of production with the chimeric enzymes CGT-CBM Amy and CGT⌬E-CBM Amy (11).…”
Section: Methodssupporting
confidence: 51%
“…To date, many attempts have been made to find an inexpensive and soluble substrate to replace ␣-and ␤-cyclodextrin as glycosyl donors for AA-2G production. For instance, we have enhanced the transformation efficiency of maltodextrin for AA-2G production through site-directed saturation mutagenesis of the Ϫ3 subsite (8), ϩ2 subsite (9), and Ϫ6 subsite residues (10) in the CGTase from Paenibacillus macerans. Furthermore, we improved the transformation efficiency of soluble starch to AA-2G by fusing the carbohydrate-binding module from Alkalimonas amylolytica ␣-amylase with CGTase from P. macerans (11).…”
mentioning
confidence: 99%
“…Control incubations were prepared by adding the same amount of Tris-HCl buffer (pH 8.3, 0.25 M) to 5 ml DTNB reagent. The cyclodextrin glycosyltransferase Y195C from Paenibacillus macerans (17) was used as a positive-control protein, as it contains one free cysteine residue.…”
Section: Methodsmentioning
confidence: 99%
“…significantly enhanced for AA-2G synthesis (9,10,28). The ϩ2 subsite is considered to be responsible for the stabilization of the glucose ring with phenyl rings at these sites (29)(30)(31)(32), and the Ϫ3 subsite has important effects on the four reactions (cyclization, coupling, disproportion, and hydrolysis) of CGTase because it is near the active site (17,33).…”
Section: Construction Of Mutants By Ismmentioning
confidence: 99%
“…In previous work, we have attempted to replace ␣-and ␤-cyclodextrins with an inexpensive and soluble substrate as a glycosyl donor for AA-2G production. For instance, we enhanced the transformation efficiency of maltodextrin for AA-2G production through site-directed saturation mutagenesis of residues K47 (9), Y195, Y260, and Q265 (10) in CGTase from Paenibacillus macerans. This outcome suggested that mutagenesis was effective for improving the specificity of CGTase toward maltodextrin by affecting the hydrogen bond interactions between the enzymes and linear substrates.…”
mentioning
confidence: 99%